(untitled) (Journal of Business Management and Accounting, 2020)
Rapid change in business environment poses threat to business survival. It is crucial to examine the core of business sustainability. This paper proposes changeless factors in response to today’s business environment. Specifically, it addresses (1) the people factor (2) the purpose factor and (3) the principle factor as the pillars through which an organization finds its stability in the sea of business change. This paper demonstrates the unchanged factors to ensure business sustainability and to achieve long term objectives. After mapping the conceptual model, the paper devotes particular attention to conceptualizing the changeless cores of business. This research contributes practical insights for managers to further understand the cores of business sustainability. Specifically, it will assist managers to have clear goals in making decisions and managing change to enhance competitiveness in the business environment.